1996
DOI: 10.1007/bf00418856
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age on resection rates and postoperative mortality in 6457 patients with colorectal cancer

Abstract: Due to the ageing of the general population, the proportion of elderly patients with colorectal cancer has increased. In a registry-based study, we evaluated the influence of age and other variables on resection rates and operative risk. Resection rates and postoperative mortality rates (30-day) were analysed in 6457 patients with colorectal cancer, diagnosed from 1985 through 1992 in hospitals connected to the Rotterdam Cancer Registry. Overall, 87% of the patients underwent resection but resection rates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 13 publications
3
31
1
Order By: Relevance
“…Previous studies on colorectal cancer have shown significant higher postoperative mortality rates in the elderly patients [3,5,6,9,11], while series on rectal cancer contradict this finding [12–14]. Emergency surgery, ASA stage and age have been described as independent risk factors influencing on postoperative mortality [5,9,11,13], but compared to colon cancer, emergency presentation is less common in rectal cancer [14].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on colorectal cancer have shown significant higher postoperative mortality rates in the elderly patients [3,5,6,9,11], while series on rectal cancer contradict this finding [12–14]. Emergency surgery, ASA stage and age have been described as independent risk factors influencing on postoperative mortality [5,9,11,13], but compared to colon cancer, emergency presentation is less common in rectal cancer [14].…”
Section: Discussionmentioning
confidence: 99%
“…The post operative mortality of patients less than 60 years was 1% and continually increased with age to about 10% for those over 80. Despite these age associated surgical outcome disparities the authors concluded that surgery should not be denied to elderly patients with acceptable preoperative risk [98]. …”
Section: Chemoprevention For Reducing the Risk Of Colorectal Cancer Riskmentioning
confidence: 99%
“…However, a significant difference was seen in those 80-84 years (8%) rising to 13% in those 85-89 and 20% in nonagenarians (p<0.001) [98]. A French review of over 8,000 cases of colon adenocarcinoma over a 20 year period defined operative mortality in those under 60 to be 1.7%, increasing to 5% in those 60-74 years and 12% in those patients over 75 (p<0.001.…”
Section: Chemoprevention For Reducing the Risk Of Colorectal Cancer Riskmentioning
confidence: 99%
“…Age, probably by association with increase comorbidity, is an important risk factor for postoperative mortality. The post‐operative mortality rate in patients who undergo surgery for colorectal cancer increases with age (3.7% in patients aged 70–79 years, 9.8% in patients aged 80 to 89 years, and 12.9% in those over 89 years) (grade B evidence) 179 …”
Section: Management Approach To Patients With Acute Lower Gastrointesmentioning
confidence: 99%